Preoperative serum hepatitis B virus DNA was a risk factor for hepatocellular carcinoma recurrence after liver transplantation. (31st December 2022) - Zhang, Dali; Feng, Danni; Ren, Minjuan; Bai, Ying; Liu, Zhenwen; Wang, Hongbo
Abstract: Background: Tumour characteristics and orthotopic liver transplantation (OLT) criteria are risks for recurrence of hepatocellular carcinoma (HCC). In Asia, most HCC is caused by chronic hepatitis B infection. Whether hepatitis B virus DNA (HBV DNA) is a risk factor for HCC recurrence after OLT is not clear. Patients and methods: In this retrospective study, we classified patients into groups of detectable and undetectable HBV DNA, non-HCC recurrence, and recurrence and performed analyses on differed characteristics between groups and risk factors for HCC recurrence after OLT. Results: Among patients who underwent OLT for HCC, 117 were secondary to CHB infection. CHB was not a risk, but advanced tumour characteristics were risk factor for HCC recurrence. In patients with CHB-HCC, 24 (20.5%) of 117 patients had HCC recurrence. Compared to patients with HBV DNA undetectable ( n = 75), patients with detectable HBV DNA ( n = 42) had higher AFP concentration ( p < .001), higher proportion of macrovascular invasion ( p = .014), greater tumour diameter ( p < .001), poorer TNM stage ( p = .017), and higher proportion of extended OLT criteria ( p = .011) and HCC recurrence ( p = .036). Preoperative HBV DNA >2000 IU/mL was an independent risk factor for HCC recurrence (OR = 8.35, 95% CI 1.40, 50.00, p = .020). HBV DNA detectable was not a risk for HCC-related death. Conclusion: Individuals with preoperative undetectable HBV DNA had advanced tumour characteristics and a higher proportion of HCC recurrence. Antiviral treatment for HCC should be performed, and HBV DNA undetectable should be obtained before OLT. But for an urgent OLT, preoperative detectable HBV DNA may not affect long-term survival. KEY MESSAGES: Patients with HBV DNA detectable had advanced tumour characteristics, a higher proportion of extended OLT criteria, and HCC-recurrence. HBV DNA >2000 IU/mL was a risk factor for HCC recurrence. HBV DNA detectable was not a risk for HCC related death; extended OLT criteria affected long-term survival.